Clear cell carcinoma of the ovary arising in a mucinous cystadenoma. Issue 12 (1st December 2000) - Dutt, N; Berney, D M
Abstract : A 57 year old woman presented complaining of increasing abdominal swelling of six months duration. A mixed solid cystic left ovarian tumour measuring 24 cm in diameter was excised. Histology showed numerous cysts lined by benign mucinous epithelium blending imperceptibly into borderline clear cell and mucinous areas that in turn merged with an invasive clear cell carcinoma. To the best of our knowledge, this is the first reported case of clear cell carcinoma arising in a mucinous cystadenoma. The implications for the previously postulated pathogenesis of these tumours are discussed.